Event Studies : Theory and Management for Planned Events - Getz, Donald, 1949-; Page, Stephen, 1963- (Events management series, 2024)
"Fully updated and revised in its fifth edition, Event Studies remains the most comprehensive book devoted to developing knowledge and theory about event management and event tourism, focusing on the study of events, the event experience and meanings associated with them. This insightful volume will be an invaluable resource for all undergraduate students of events studies throughout their degree programmes"--